2000
DOI: 10.1007/s004180000151
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intracellular nitric oxide using a combination of aldehyde fixatives with 4,5-diaminofluorescein diacetate

Abstract: Using 4,5-diaminofluorescein diacetate (DAF-2DA), which was recently developed for the detection of intracellular nitric oxide (NO) in living cells, we examined the sensitivity of intracellular NO in cells treated with some fixatives. Cultured human umbilical vein endothelial cells loaded with DAF-2DA in the presence of 10 -6 M acetylcholine showed intense fluorescence when fixed in paraformaldehyde or glutaraldehyde, but no fluorescence could be detected after fixation in ethanol or acetone. Fluorescence gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…In these experiments, 500 mM H 2 O 2 was applied in instantaneous ROS dynamics observations lasting for 5 min (to collect fluorescence signal with enough intensity changes in confocal microscope), while 0e500 H 2 O 2 was applied in others studies lasting for several hours. (Bindokas et al, 1996); DAF/AM can also specifically react with intracellular NO (Sugimoto et al, 2000). Unfortunately, there is currently no specific probe for H 2 O 2 in living cells.…”
Section: Methodsmentioning
confidence: 99%
“…In these experiments, 500 mM H 2 O 2 was applied in instantaneous ROS dynamics observations lasting for 5 min (to collect fluorescence signal with enough intensity changes in confocal microscope), while 0e500 H 2 O 2 was applied in others studies lasting for several hours. (Bindokas et al, 1996); DAF/AM can also specifically react with intracellular NO (Sugimoto et al, 2000). Unfortunately, there is currently no specific probe for H 2 O 2 in living cells.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were then anesthetized in seawater containing 2% ethanol, dissected to expose the ventral surface of the light organ, and viewed with a Zeiss 510 laser scanning confocal microscope (LSM). In experiments for the detection of NO in fixed tissues (Sugimoto et al ., 2000), hatchlings were fixed as described (see above, The detection of NOS activity by the NADPH‐diaphorase reaction ), rinsed with mPBS, stained with DAF, and viewed by LSM. Physiological analyses of V. fischeri have shown that it neither produces NO nor uses it as a terminal electron acceptor (E.G.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular NO was examined in HUVECs loaded with NOsensitive fluorescent dye diaminofluorescein-2 diacetate (DAF2DA; 5 lmol/L), with or without acetylcholine (ACh) treatment (1 lmol/L, 20 minutes). 19 In transfected HUVECs, NO was detected by using 4-amino-5-methylmino-2 0 ,7 0 -difluorofluorescein (DAF-FM) diacetate. Nuclei were stained with 4 0 ,6-diamidino-2-phenylindole (DAPI; 1 lmol/L).…”
Section: Confocal Fluorescence Microscopymentioning
confidence: 99%